Efficiency of channel codes for different fading models in 5G enhanced mobile broadband scenario - Khmelevsky, Mikhail; Kazakov, Gennady (International Journal of Electrical and Computer Engineering (IJECE), 2025)
In urban environments, 5th generation (5G) signals are subject to interference, multiple propagation and thermal noise, resulting in a significant amount of errors. In this regard, channel coding is applied, which allows to increase the reliability of the transmitted message. This work focuses on comparing the performance of low-density parity check (LDPC) and polar codes standardized by the 3rd generation partnership project (3GPP) for application in 5G networks in physical downlink shared channel (PDSCH) under multipath propagation conditions in enhanced mobile broadband (eMBB) scenario. The performance of the codes under study was investigated considering all signal processing operations implemented in hardware in 5G channels. We used clustered delay line (CDL) and tapped delay line (TDL) models as propagation channel models. Channel configuration and selection of signal parameters were based on the analysis of commercially launched 5G networks. One of the simulations results we observed was the high signal-to-noise ratio (SNR) required to transmit the signal while ensuring a given block error rate (BLER). Polar codes demonstrated both a gain in coding over LDPC codes and a loss in decoding delay of the received signal due to a more complex decoding algorithm.